Alfabetização científica no ensino de ciências: caminhos e desafios - OLIVEIRA FILHA, Roselene Hianes (2019)
This monograph is the result of a work that aims to develop a study on science literacy in Science teaching, showing its paths and challenges. It is intended to expose science teaching under the optics of scientific literacy in parallel to the teaching of science taught by elementary school teachers in the classroom. The methodology of the work took place of bibliographic survey, which was made use of authors such as Chassot (2003), Krasilchik (1987) Lorenzetti and Delizoicov (2001), Carvalho (2004), Bizzo (2009) among others, in addition to the thorough readings, in search of more Information. It was used, field research, where teachers were interviewed in the lower elementary school at a school of the state Public education network in Belém-PA. This research allows us to reflect on how the teaching of science in public schools is being worked. It is necessary that teachers, educators seek more efficient and attractive methodologies for the work to reach its main focus that are people literate scientifically, because, it is through the scientific literacy that children are Made possible to read the world, to understand the space where they are inserted and will intervene in the environment, so the teaching of science can collaborate for the citizen formation promoting the broad development of the child.